2016
DOI: 10.1159/000449390
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Antimuscarinics Alone or in Combination with Alpha-Blockers for the Treatment of Ureteral Stent-Related Symptoms: A Systematic Review and Meta-Analysis

Abstract: Introduction and Aim: The purpose of this meta-analysis was to evaluate the efficacy of antimuscarinics alone or in combination with alpha-blockers for the treatment of ureteral stent-related symptoms. Methods: The databases MEDLINE, EMBASE, PubMed, the Cochrane Controlled Trial Register of Controlled Trials from 2000 to February 2016 were searched to identify randomized controlled trials that referred to the use of a combination of antimuscarinics and alpha-blockers for the treatment of ureteral stent-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…Numerous drugs had been tried to relieve these symptoms like alpha blockers, anticholinergics, phosphodiesterase inhibitors (PDE5Is) and analgesics. [6,7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] Silodosin is a highly selective alpha-1 adrenergic receptor antagonist which is used in the treatment of lower urinary tract symptoms (LUTS). Alpha-1 adrenergic receptors are densely found in the smooth muscle cells of the lower urinary tract, and silodosin relaxes them and improves the SRS, and various studies had also shown similar effect.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous drugs had been tried to relieve these symptoms like alpha blockers, anticholinergics, phosphodiesterase inhibitors (PDE5Is) and analgesics. [6,7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] Silodosin is a highly selective alpha-1 adrenergic receptor antagonist which is used in the treatment of lower urinary tract symptoms (LUTS). Alpha-1 adrenergic receptors are densely found in the smooth muscle cells of the lower urinary tract, and silodosin relaxes them and improves the SRS, and various studies had also shown similar effect.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] Anticholinergics can also improve SRS by reducing the involuntary bladder contraction that occurs due to trigone irritation. [18][19][20][21][22][23][24][25] PDE5Is increase levels of cGMP that will lead to relaxation of the smooth muscle of ureter and reduces SRS. [6,26] The aim of our study was to evaluate the efficacy and safety of silodosin, solifenacin, tadalafil, and their combinations in reducing DJ stent-related LUTS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesized that less severe ureteric stent-related symptoms would result in the patients ignoring and forgetting about the presence of DJs inside their bodies, especially in cases in which the DJs were newly indwelled. Alpha blockers are reported to improve ureteric stent-related symptoms 9 ; therefore, we tested the association of postoperative prescriptions of alpha blockers with forgotten DJs. A T test, Fisher's exact test, and Pearson's chi square test were applied for statistical analysis.…”
Section: Methodsmentioning
confidence: 99%